B0–B¯0 mixing in supersymmetry with gauged baryon and lepton numbers - Fei Sun (Nuclear Physics B, 2014)
We perform an analysis on B0–B¯0 mixing in the extension of the minimal supersymmetric standard model where baryon and lepton numbers are local gauge symmetries (BLMSSM) by using the effective Hamiltonian method. And the constraint of a 125 GeV Higgs to the parameter space has also been considered. The numerical results indicate that the contributions of the extra particles can be sizeable in B0–B¯0 mixing. For certain parameter sets, the theoretical prediction of mass differences ΔmB agrees with the current experimental result. Furthermore, B0–B¯0 mixing in the BLMSSM can preliminarily constrain the parameter space. With the development of more precise theoretical analysis and experimental determinations, the B0–B¯0 mixing in the BLMSSM will have a clearer picture and the parameter space in this model will also be further constrained.